Designing a collaborative visual analytics system to support users' continuous analytical processes. - Chang, Remco.; Jeong, Dong Hyun.; Ji, Soo-Yeon.; Suma, Evan A.; Yu, Byunggu. (Tufts University. Tisch Library., 2017)
In recent, numerous useful visual analytics tools have been designed to help domain experts solve analytical problems. However, most of the tools do not reflect the nature of solving real-world analytical tasks collaboratively because they have been designed for single users in desktop environments. In this paper, a complete visual analytics system is designed for solving real-world tasks having two integrated components: a single-user desktop system and an extended system suitable for a collaborative environment. Specifically, we designed a collaborative touch-table application (iPCA-CE) by adopting an existing single-user desktop analytical tool (iPCA) With the system, users can actively transit from individual desktop to shared collaborative environments without losing track of their analysis. They can also switch their analytical processes from collaborative to single-user workflows. To understand the usefulness of the system for solving analytical problems, we conducted a user study in both desktop and collaborative environments. From this study, we found that both applications are useful for solving analytical problems individually and collaboratively in different environments.